Lymphadenitis and Fever: First Presentation of Kawasaki Disease - Şule Gökçe; Pelin Elibol; Güldane Koturoğlu; Yasemin Özdemir Şahan; Zülal Ülger Tutar (Journal of Pediatric Research, 2017)
Kawasaki disease is a vasculitis of infant and childhood period. Diagnosis of Kawasaki disease is based on clinical criteria including cervical lymphadenopathy. Here we reported a 3.5-year-old boy presenting with Kawasaki disease mimicking bacterial lymphadenitis and fever. If a child presents with lymphadenopathy only which is unresponsive to antibiotics, Kawasaki disease should be considered.